2007
DOI: 10.1002/pamm.200700908
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical behavior of pseudoelastic NiTi shape memory alloys

Abstract: The thermomechanical behavior of polycrystalline Ni-rich pseudoelastic NiTi shape memory alloys is analyzed. Special focus is on regions within the stress strain diagram which are regarded as linear elastic in common phenomenological material models, i.e. the region between zero stress and the beginning of the pseudoelastic plateau as well as the region within the hysteresis. In both cases, severe temperature changes can be observed. A possible explanation for this effect is twofold: On the one hand, it might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This finding implies that beside the applied strain rate, the surrounding ambient affects the temperature variations too. A similar conclusion can be drawn based on the works of Morin et al (2011) and Luig et al (2007). Morin et al (2011) observed that the rate dependency disappears for low to moderate strain rates when the temperature of the test sample is kept constant.…”
Section: Introductionsupporting
confidence: 77%
“…This finding implies that beside the applied strain rate, the surrounding ambient affects the temperature variations too. A similar conclusion can be drawn based on the works of Morin et al (2011) and Luig et al (2007). Morin et al (2011) observed that the rate dependency disappears for low to moderate strain rates when the temperature of the test sample is kept constant.…”
Section: Introductionsupporting
confidence: 77%